Investigating the employment motivation, job satisfaction, and dissatisfaction of international high school teachers in China: the impact of the COVID-19 pandemic - Mo, Junhua; Morris, Gareth (Frontiers in Psychology, 2024)
International education has become increasingly challenging to manage in an unpredictable world beset by pandemics, regional disputes and evolving market practices. The last few decades have seen a huge demand for international education in China, and numerous acclaimed international brand names set up operations in China's K12 schooling sector. However, the COVID-19 pandemic exerted a noticeably negative impact on international high schools and their staff in China, and exacerbated a difficult period of management for these institutions. Interestingly, but perhaps unsurprisingly, the actual operation of these educational workplaces remains under investigated in academic studies. This paper therefore attempts to examine international high schools in China by focusing on their teachers and their associated employment motivation, job satisfaction and dissatisfaction which has been perceptibly influenced by the impact of the COVID-19 pandemic. Through a qualitative, case-study approach which adopted semi-structured interviews, an acclaimed British high school, now closed, was investigated. The study found that international high school teachers were driven by diverse work motives such as the school's reputation, values, salary, environment and chances for career development. Their job satisfaction was also multifaceted, and their dissatisfaction in certain areas concerning. That is, they derived an early satisfaction from a range of facets, such as the students, class sizes, initial workloads, autonomy and collegiality. However, these early feelings were replaced by a sense of dissatisfaction and noticeable unhappiness resulting from leadership changes and subsequent management practices, increased workload, unmet employment package expectations and obligations, as well as limited professional development opportunities. This study highlights the importance of recruiting well, generating the right starting and longer-term conditions, retaining key staff and managing astutely. The work will be of interest to policy makers, investors, leaders, managers and staff alike. It will also extend educational research in the areas of teacher motivation, satisfaction and dissatisfaction, and in particular in China in international K12 settings.